Investigation on the effectiveness of mouth-washing using laban leaves (Vitex pinnata) steeping water in reducing plaque accumulation: a study in state elementary school 1 Pagar Air, Aceh Besar - Nuraskin, Cut Aja; Faisal, T. Iskandar; ., Reca; Salfiyadi, Teuku; Mardiah, Ainun (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Dental and oral diseases that are commonly suffered by Indonesian people, are dental caries and periodontal disease. Dental plaque is the primary cause of the periodontal disease and dental caries. The diseases can be prevented by inhibiting the formation of dental plaque using a mouthwash. One of the ways in removing dental plaque is by mouth washing using laban leaves (Vitex pinnata Linn) steeping water. Laban leaves contain alkaloids, flavonoids, saponins, and tannins which can inhibit the growth of Streptococcus mutans so that it capable of removing dental plaque naturally. Bio-ingredients have been long used in health sector for preventive, curative, and rehabilitative treatments. Methods: Experimental research with pre- and post-tests design using proposing sampling technique, where 56 people were taken as samples. The samples were divided into 2 groups which receiving different treatments. Group 1 was instructed to do mouth washing with laban leaves steeping water, while Group 2 was with water. Each of students did the mouth washing for 30 s (20 ml). Results: based on the comparison of the dental plaque index (before and after the mouth washing using laban leaves steeping water) it is revealed that the steeping water of laban leaves was effective in reducing the plaque index with p value of 0.000 (<α=0.05). Conclusions: mouth washing using the laban leaves steeping water was effective in reducing the plaque accumulation. We then recommend a further study to investigate the potential of laban leave to be used in a mouthwash.